Occurrence and survival of pathogens at different sludge depths in unlined pit latrines in Kampala slums - Nabateesa, Sylivia; Zziwa, Ahamada; Kabenge, Isa; Kambugu, Robert; Wanyama, Joshua; Komakech, Allan John (Water Sa, 2017)
Occurrence and survival of pathogens in faecal sludge was investigated in unlined pit latrines at varying depths in peri-urban areas of Kampala city, Uganda. A total of 55 unlined pit latrines, 7 private and 8 rental unlined pit latrines were sampled in the first and second phases (representing the rainy season) and 40 pits in the third phase (representing dry season), and analysed for indicator organisms and pathogens from 4 pit latrine sludge layers, at depths of 0, 0.5, 1.0 and 1.5 m, following APHA standard methods. Physico-chemical parameters of the faecal sludge were also measured. Three sampling phases were undertaken to determine the effect of seasonal variation. Results indicate that the mean temperature and pH were 25.4 ± 1.14°C and 8.0 ± 1.5, respectively; and moisture content increased with pit sludge depth, except between Depths 3 and 4. Average moisture content was 86.3 ± 3%. The measured parameters varied significantly (P > 0.05) between seasons. The mean reduction in total coliforms, thermo-tolerant coliforms, E. coli, and faecal enterococci with sludge depth was significant at all depths (P < 0.05), but the least significant difference was not significant at depth levels of 1.0 m and 1.5 m. Salmonella was only detected at the top layer of faecal sludge in 60% of Phase 2 samples and in only 20% of the samples in Phase 3. About 200–4 100 eggs/g of strongyles were found in 98% of the samples and 100–1 600 eggs/g of ascarids in 55% of the samples. Temperature, pH and moisture content did not show a significant correlation with observed reductions of indicators and pathogens. With extrapolation of the generated regression models, a pit of 8 m can be recommended for reduction of bacteria. It is recommended that protective field gear be used during pit emptying and that faecal sludge treatment should be done to reduce pathogens before disposal into the environment.
Keywords: Pathogens; Indicator organisms; Faecal sludge; Unlined pit latrine; Water contamination